An Effient Synthesis of Pyrrolo[1, 2‐a]quinoxaline Derivatives via Isocyanide Insertion into the N−H Bond of 2‐(1H‐pyrrol‐1‐yl)anilines. Issue 11 (30th September 2021) - Luo, Liangliang; Xiong, Tong; Zhou, Liyan; Zeng, Qin; Xiao, You‐Cai; Chen, Fen‐Er
Abstract: We describe a highly efficient cyclization of substituted 2‐(1 H ‐pyrrol‐1‐yl)anilines with isocyanides. Various pyrrolo[1, 2‐ a ]quinoxalines and 4‐aminopyrrolo[1, 2‐ a ]quinoxalines were obtained by Lewis acid (TMSCl) or transition‐metal (palladium) catalyzed isocyanide insertion in good to high yields. The notable feature of this protocol includes its mild reaction condition, diverse products and broad functional group tolerance. Abstract : A highly efficient cyclization of substituted 2‐(1 H ‐pyrrol‐1‐yl)anilines with isocyanides has been achieved. Various pyrrolo[1, 2‐ a ]quinoxalines and 4‐aminopyrrolo[1, 2‐ a ]quinoxalines were obtained by Lewis acid (TMSCl) or transition‐metal (palladium) catalyzed isocyanide insertion in good to high yields.